Study protocol on establishment of sentinel sites network for contraceptive and abortion trends, needs and utilization of services in Zika virus affected countries - Ali, Moazzam (Reprod Health, 2017)
BACKGROUND: ZIKV(Zika Virus) during pregnancy can result in many adverse events such as fetal deaths or newborns with congenital abnormalities including microcephaly and other neural irregularities. Due to these harmful outcomes of pregnancy associated with the Zika virus, we can expect to see a change in the type and scale of demand for family planning and safe abortion services in areas affected by the Zika virus. The monitoring and reporting capacities of the local health clinics in these areas could benefit from the introduction of infrastructural improvements necessary to establish a sentinel site network. Through these sites, the WHO will collect data on the situation from local health professionals to get real time information from the population group and act accordingly to mitigate the consequences of the Zika virus outbreak in a localized and culturally appropriate way. The objectives are to establish a sentinel sites surveillance network for reporting on uptake and utilization of contraception and safe abortion care services; to strengthen monitoring, and data quality assurance in the selected sentinel surveillance sites; and finally to assess the contraception and safe abortion care service utilization trends in the affected sites on a regular basis. METHODS: The proposal includes a set of objectives and actions that enable the creation of a set of criteria for the selection of the sentinel sites, as well the implementation of monitoring and reporting systems that will be used in data collection. DISCUSSION: The data collected will be used to better understand the changing demand for family planning and safe abortion needs. This will ultimately be used to inform local health workers and policy makers as to how best to track the continued Zika virus outbreak and mitigate the consequences. The learning from establishment of surveillance sentinel sites will help to strengthen health systems at regional and subregional levels that are more adaptable and capable of providing reproductive healthcare services and of responding to future emergencies.